Is there an excess risk for colorectal cancer in patients with ulcerative colitis and concomitant primary sclerosing cholangitis? A population based study. Issue 4 (1st October 1997) - Kornfeld, D; Ekbom, A; Ihre, T
Abstract : Background —Patients with ulcerative colitis have an increased risk of colorectal cancer. Duration, age, and extent of the disease at diagnosis are the only established risk factors. Patients with ulcerative colitis and concomitant primary sclerosing cholangitis (PSC) have been reported to have a higher frequency of colonic DNA aneuploidy and/or dysplasia than expected, findings indicating an increased risk of colorectal cancer compared with other patients with ulcerative colitis. Methods —A population based cohort consisting of 125 patients with a verified diagnosis of PSC was followed up by linkage to the Swedish Cancer Registry for the occurrence of colorectal cancer. Results —There were 12 colorectal cancers. Six cancers were diagnosed prior to the diagnosis of PSC. Among the 104 patients with an intact colon at the time of the diagnosis of PSC there was a cumulative risk for colorectal cancer of 16% after 10 years. Among the 58 patients with a diagnosis of ulcerative colitis and colorectal cancer prior to the diagnosis of PSC, there were five colorectal cancers corresponding to a cumulative risk of 25% after 10 years. Conclusions —Patients with ulcerative colitis and concomitant PSC seem to constitute a subgroup with a high risk for colorectal cancer.